Teaching students about chemical elements using daily-life contexts - Franco-Mariscal, Antonio Joaquín; España-Ramos, Enrique; Blanco-López, Ángel (My University, 2017)
Learning the names and symbols for chemical elements is a task that students often find dull, although it is of crucial importance for understanding chemistry. In this respect, the use of games or similar play activities could make the learning experience more enjoyable. This paper presents the results of a study in which two tasks involving play (TIPs) and based on daily-life contexts (football and the home) were used to teach the names and symbols of chemical elements. The experimental group comprised 38 year-10 students who studied this topic through a teaching unit built around the TIPs. A control group of 67 year-10 students followed a traditional teaching approach to the same topic. The effectiveness of the TIPs was assessed using three items, administered pre- and post-test, that explored students’ knowledge about metallic and non-metallic elements and their ability to identify them in their everyday environment. Following the TIP-based teaching unit, students in the experimental group gave a higher percentage of appropriate answers, with the Wilcoxon test indicating significant post-test differences for all three items. However, the Kolgomorov-Smirnov test indicated that the experimental and control groups only differed significantly at post-test in their ability to give the names and symbols of non-metals, with the experimental group performing better. Memorising the names and symbols of chemical elements is a complex task for students, and identifying their presence in everyday environments appears to be particularly difficult. However, the results suggest that the use of TIPs linked to daily-life contexts could help students with their learning of this topic.
Keywords: Tabla periódica (Química); Periodic table; Educational games; Daily-life contexts